2011
DOI: 10.1007/s11060-011-0643-0
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged temozolomide for treatment of glioblastoma: preliminary clinical results and prognostic value of p53 overexpression

Abstract: We report retrospective data on the feasibility and efficacy of prolonging adjuvant temozolomide (TMZ) more than 6 months after chemoradiotherapy completion in patients with glioblastoma (GBM). Molecular prognostic factors were assessed. Data from 46 patients were reviewed. Patients received postoperative irradiation, 60 Gy in 30 fractions, combined with concurrent TMZ, 75 mg/m(2). Four weeks later, adjuvant TMZ was prescribed, 150-200 mg/m(2) for a total of 24 cycles unless there was progression or toxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 14 publications
4
24
1
Order By: Relevance
“…Although initially identified in tumors following radiation or genotoxic chemotherapy (9-11), TIS might also be induced at lower drug doses, in contrast to the higher doses at which DNA damage and apoptotic responses are elicited. Temozolomide is widely used for the treatment of glioblastoma (22,23), and has been reported to induce senescence without apoptosis in melanoma cells (24). The present study demonstrated that carnitine induced senescence in glioma cells.…”
Section: Discussionsupporting
confidence: 63%
“…Although initially identified in tumors following radiation or genotoxic chemotherapy (9-11), TIS might also be induced at lower drug doses, in contrast to the higher doses at which DNA damage and apoptotic responses are elicited. Temozolomide is widely used for the treatment of glioblastoma (22,23), and has been reported to induce senescence without apoptosis in melanoma cells (24). The present study demonstrated that carnitine induced senescence in glioma cells.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies support an effect of p53 status on improving prognosis, 31,39,40 while others show a limited impact on clinical outcome. 13,19,45 One study of 46 patients who had received adjuvant radiochemotherapy showed im-biomarkers in glioblastoma proved median PFS (9.3 vs 7 months) in samples without p53 overexpression; however, another study of 220 GBMs did not show a significant difference in median survival between wild-type and mutant p53 GBM tumors (17.0 vs 14.7 months).…”
Section: 32mentioning
confidence: 99%
“…Stricter adherence to adjuvant TMZ in the setting of early post-chemoRT imaging changes (some of which represents PsP) may in part have contributed to the improved outcomes on recent NABTT Phase II studies [16]. However, even with continuation of adjuvant TMZ beyond 6 months, only approximately 35% of the patients remain without progression at 12 months [20]. Patients with progressive HGG should ideally be enrolled in clinical trials.…”
Section: Clinical Significancementioning
confidence: 99%